Preservasi Imago Jantan Ulat Sutera Liar Attacus Atlas (Lepidoptera: Saturniidae) - Eko Prasetyo Nugroho; Damiana Rita Ekastuti; Raden Iis Arifiantini (Jurnal Ilmu Pertanian Indonesia, 2014)
Wild silkworm (Attacus atlas) has high economic value. There is a problem in rearing wild silkworm Attacus atlas, the emergence of males and females imagoes are not the same. The aim of this research was to study the survival lifetime and the sperm of the male imago. This research used randomized design experiment, with two treatments of storage temperature (room temperature 27 °C and cool storage temperature 5 °C) and eight repetitions. Survival of male imago, sperm survival, and imago body weight had been measured. The results showed that cool temperature (5 °C) could to extend significantly (P<0,01) the survival lifetime of male imago and the sperm of male imago A. atlas up to 11.5 ± 0.7 days. There is a positive correlation between body weight and lifetime of male imago of wild silkworm A. atlas, so the lifetime of male imago is predicable from their body weight.